Factores Biosocioculturales y su Relación con la Hipertensión Inducida por el Embarazo Hospital Regional Docente de Trujillo-2006 - Grozo Angeles, Doris Angelita (2006)
The following investigation witch is a cuantitative restrospective correlational type, was carried out at Hospital Regional Docente de Trujillo, during the month: may 2005- august 2006; with the purpose to determinate the existent relationship between biosociocultural factors: age, nuliparity , prenatal controland level instruction about pregnancy. The sample was constituted by 2 groups: group 1: 138 clinical histories from high blood pregnancy and group II: 138 clinical histories from pregnant women without high blood pregnancy the information was obtain by instrument made by the autor. The obtain data was process following the Chi cuadrado criterial. The high blood preasure pregnant women had a mayor porcent image19 (51.45%), being the first time pregmant women (64.49%) on the high blood pregnancy group diferencians from the pregmant women without without high blood pregnancy that were most likely to be between ages 20 to 35 years old(74.64%), multiparities (52.17%), About prenatal control and level of instruction, there is no statistical diference among bouth cases. There for the only variables that the percentages are lalike influence high blood preassure induce by Pregnancy are age and parity. Passwords: Biosociocultural Factors, High blood Preassure Induce by Pregnancy